Virtual Simulators in The Teaching-Learning of Chemistry and Physics: A Systematic Review of The Literature - Yaipén-Gonzales, Héctor Filamir; Joo, Luis Alexander Pulido; Montenegro-Camacho, Luis; Soto, Rosario Mercedes Huerta; Cassano, Pietro Pablo Guissepi Dondero; Mejia, Percy Junior Castro (International Journal of Membrane Science and Technology, 2023)
The objective of this study was to describe quantitative metrics related to publications on the advantages offered by virtual simulators for the teaching-learning of students in the subjects of Physics and Chemistry, in different databases such as Ebsco, Dialnet, Scielo, DOAJ, including the time period filter. from 2019 to 2023. In this sense, the search was carried out by consulting the words "Virtual simulators", "Virtual reality", "Exact sciences", "Chemistry", "Physics", in the aforementioned databases. Then, the studies were filtered according to the inclusion criteria, which are open access documents and the subject in the database itself, for subsequent review of the literature. At the end of the review, the last filter was performed by exclusion criteria, leaving 9 studies as a final result. It was evidenced that in 2022 the largest number of publications was made, with a total of 4 and also the highest peak of scientific production. Likewise, it was recorded that scientific research on the subject is also carried out in Peru, but it is necessary to deepen it; However, this number of publications shows a scarce scientific production in Latin America. On the other hand, the results of the most frequent keywords in the studies carried out on this topic were chemistry and learning. Finally, it is concluded that there is a shortage of studies that relate both physics and chemistry. Although there are studies that show us an individualized analysis for each variable.